1983
DOI: 10.2527/jas1983.5751117x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Parameters Estimated From Nebraska Specific-Pathogen-Free Swine Field Records

Abstract: SummaryRecords collected during 1971 through 1979 from 101,606 hogs raised in 18 Nebraska Specific Pathogen Free herds were analyzed. Traits considered were backfat at 100 kg (BF), weight at 140 d of age (WT) and, in some analyses, number of live pigs/litter at birth (NBA). The phenotypic correlation of BF and WT, averaged across herds, was -.07. The correlations between BF and NBA and between WT and NBA were .04 and -.05, respectively. Average phenotypic standard deviations for BF, WT and NBA were 2.6 mm, 8.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
6

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 10 publications
3
13
0
6
Order By: Relevance
“…Therefore, the discrepancy between estimates of heritability from the current study and the values recommended by NSIF cannot be explained solely by bias due to selection of progeny. David et al (1983) suggested that the low estimates of heritability that they obtained from some of the same data compared to results from experiments might be due to more heterogeneous environments for SPF pigs compared to pigs from experiments. Another explanation is that contemporary groups probably are less correctly specified in private seedstock herds than in experimental herds.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, the discrepancy between estimates of heritability from the current study and the values recommended by NSIF cannot be explained solely by bias due to selection of progeny. David et al (1983) suggested that the low estimates of heritability that they obtained from some of the same data compared to results from experiments might be due to more heterogeneous environments for SPF pigs compared to pigs from experiments. Another explanation is that contemporary groups probably are less correctly specified in private seedstock herds than in experimental herds.…”
Section: Resultsmentioning
confidence: 87%
“…Estimates of heritability in the literature vary widely (Hutchens and Hintz, 1981;David et al, 1983;Kennedy et al, 1985;Bereskin, 1987). In spite of this, the general conclusion of swine geneticists is that h 2 is near .35 for days to 104.4 kg and .40 for backfat as indicated by the National Swine Improvement Federation (NSIF) guidelines (1987).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations